SISTEM KERJA SAMA TRAVEL AGENT PENJOR BALI DENGAN KEBERADAAN GEKKO THE OCEAN CAFE? DI PANTAI KEDONGANAN KECAMATAN KUTA SELATAN KABUPATEN BADUNG - Agus Darmawan, I Putu; Suwena, I Ketut; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 3 No 2 (2015): Jurnal IPTA (December 2015)DO - 10.24843/IPTA.2015.v03.i02.p12, 2015)
To develop cafe? industry in Kedonganan, cafe? managers work together with Travel Agent to maintain cafe? industry. One of cooperation is conducted in collaboration with Travel Agent, because it has been known that Kedonganan Cafe? is one of the including culinary destinations for the package of Travel Agent. Data collection technique use observation, in-depth interviews, and library research. Type of data used is quantitative data and qualitative data. Data sources use primary data and secondary data. Data analysis method is descriptive qualitative analysis using the SWOT. Results of discussions conducted with SWOT that SO strategy is a strategy to increase cooperation with the Travel Agent, WO strategy is a strategy of delivering the best service and increase promotion, ST strategy is a strategy for cooperation contract agreements so that there are rules that bind both parties, WT strategy is a strategy to maintain and seafood prices set by mutual agreement so that the entire cafe? manager harmonious relationship between fellow managers.The suggestion in this paper is in the doing that the agreement has been agreed to include regulations that govern both parties, preferably whole cafe? manager called a meeting together to set prices and package alacarte seafood for Travel Agent.
Keywords: Cafe? Industry, Cooperation System, Strategy